2013
DOI: 10.1111/chd.12129
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Dofetilide for the Treatment of Atrial Tachyarrhythmias in Adults with Congenital Heart Disease

Abstract: D should be considered a pharmacologic alternative when adult patients with CHD develop AT. D does not depress conduction, sinus node, or ventricular function but needs close monitoring for potential ventricular pro-arrhythmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…The success rate of AAD without DCCV for terminating atrial arrhythmia has been reported as 70% for sotalol and dofetilide in several case series. 1214 The present study suggests that DCCV is comparable with and may be superior to AAD conversion rates reported for acute treatment of atrial arrhythmia.…”
Section: Discussionsupporting
confidence: 73%
“…The success rate of AAD without DCCV for terminating atrial arrhythmia has been reported as 70% for sotalol and dofetilide in several case series. 1214 The present study suggests that DCCV is comparable with and may be superior to AAD conversion rates reported for acute treatment of atrial arrhythmia.…”
Section: Discussionsupporting
confidence: 73%
“…The success rate of AAD without DCCV for terminating atrial arrhythmia has been reported as 70% for sotalol and dofetilide in several case series. [12][13][14] The present study suggests that DCCV is comparable with and may be superior to AAD conversion rates reported for acute treatment of atrial arrhythmia.…”
Section: Discussionsupporting
confidence: 73%
“…310 Atrial flutter can occur in clinical settings similar to those associated with AF, and atrial flutter can be triggered by AT or AF. 121,311 It is common for AF and atrial flutter to coexist in the same patient. After CTI ablation, 22% to 50% of patients have been reported to develop AF after a mean follow-up of 14 to 30 months, although 1 study reported a much higher rate of AF development, with 82% of patients treated by catheter ablation for atrial flutter manifesting AF within 5 years.…”
Section: Cavotricuspid Isthmus-dependent Atrial Fluttermentioning
confidence: 99%